Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae) - Allegro, Gianni; Giachino, Pier Mauro (Zootaxa, 2016)
Nine new Trechisibus species are described, four from Central Peru (T. huascarani n. sp. and T. recuayi n. sp. from Dept. Ancash, T. curtii n. sp. and T. lemairei n. sp. from Dept. Huanuco) and five from Patagonian Argentina, Province of Rio Negro (T. brevis n. sp., T. longipenis n. sp., T. parvulus n. sp., T. sciakyi n. sp., T. striatus n. sp.).